'I did it my way': customisation and practical compliance with EU policies. Issue 3 (4th March 2022) - Zhelyazkova, Asya; Thomann, Eva
ABSTRACT: By tackling shared problems through concerted policies, the European Union (EU) is thought to have a superior output legitimacy. However, EU policies change as they are being 'customised' during the implementation process. How do such patterns of 'differentiated implementation' affect EU governance in practice? While some studies highlight the danger of 'watering down' the objectives of EU law, others emphasise the role of decentralised problem-solving. We analyse how customisation affects states' practical compliance with EU anti-discrimination, environmental, and justice and home affairs directives in 27 member states (excluding Croatia) between 2007 and 2013. The findings show that customised density (higher number of rules than prescribed by the EU directives) reduces practical compliance. Conversely, customised restrictiveness (stricter requirements than the EU directives) improves practical compliance. In contrast to earlier implementation research, we conclude that literal implementation is not the best form to ensure practical implementation.